Construction Management in the New Building Project for the Haji Medan General Hospital - Nur Anisa Syafira Bestari; Ridho Bayu Aji (Penerbit Hellow Pustaka, 2024)
Improving health services is one of the priorities in North Sumatra Province, a province that is currently carrying out a lot of development, one of which is the construction of hospitals which are used to meet the health needs of the people in North Sumatra. The development process carried out is a form of service improvement. This study was carried out to analyze the development management of RSU Haji Medan which was carried out by PT. KSO Adhi-Penta. Good construction management needs to be implemented to ensure that work can be completed according to the implementation schedule. The problem formulation in this research discusses three research focuses, namely: 1) Supervision of project management at RSU Haji Medan, 2) Arrangement of human and material resources, 3) Arrangement of scheduling of RSU Haji Medan project activities. The analytical method in this research was carried out using the and Build principle. The Design and Build method provides opportunities to increase time and cost efficiency. The results of this research are: 1) Construction supervision management ensures that all construction activities take place in accordance with the plans, specifications and standards that have been set. 2) Human resources (HR) and material factors cannot be separated because they will have an impact on the quality and running of the business activities carried out. Not only that, the quality of human resources and materials will provide maximum results. 3) PT. KSO Adhi-Penta's target for completion and implementation was successful in achieving the progress that had been determined step by step in accordance with the plan, this indicates that in the construction of RSU Haji Medan, the contractor or developer was successful in implementing management principles well.